Roadmap on electromagnetic metamaterials and metasurfaces - Cui, Tie Jun; Zhang, Shuang; Alu, Andrea; Wegener, Martin; Pendry, John; Luo, Jie; Lai, Yun; Wang, Zuojia; Lin, Xiao; Chen, Hongsheng; Chen, Ping; Wu, Rui-Xin; et al. (Journal of Physics: Photonics)
Keywords: Electrical and Electronic Engineering; Atomic and Molecular Physics; and Optics; Electronic; Optical and Magnetic Materials

Stickstoff basierte Flammschutzmittel für das Lasersintern: Optimierung und Analyse der Recyclingfähigkeit (Studienarbeit) - Hücker, Lars

Phosphorhaltige Lasersinter-Materialien mit Flammschutzwirkung: Optimierung und Analyse der Recyclingfähigkeit (Studienarbeit) - Schulz, Maurice

Sorgeprakiken der Online-Rechten – Jordan Petersons Therapeutik des ,Self-Authoring' - Degeling, Jasmin; Haffke, Maren (digital:gender - de:mapping affect. Eine spekulative Kartographie)

Fast Multiobjective Gradient Methods with Nesterov Acceleration via Inertial Gradient-Like Systems - Sonntag, Konstantin; Peitz, Sebastian (Journal of Optimization Theory and Applications)
We derive efficient algorithms to compute weakly Pareto optimal solutions for smooth, convex and unconstrained multiobjective optimization problems in general Hilbert spaces. To this end, we define a novel inertial gradient-like dynamical system in the multiobjective setting, which trajectories converge weakly to Pareto optimal solutions. Discretization of this system yields an inertial multiobjective algorithm which generates sequences that converge weakly to Pareto optimal solutions. We employ Nesterov acceleration to define an algorithm with an improved convergence rate compared to the plain multiobjective steepest descent method (Algorithm 1). A further improvement in terms of efficiency is achieved by avoiding the solution of a quadratic subproblem to compute a common step direction for all objective functions, which is usually required in first-order methods. Using a different discretization of our inertial gradient-like dynamical system, we obtain an accelerated multiobjective gradient method that does not require the solution of a subproblem in each step (Algorithm 2). While this algorithm does not converge in general, it yields good results on test problems while being faster than standard steepest descent.

A Descent Method for Nonsmooth Multiobjective Optimization in Hilbert Spaces - Sonntag, Konstantin; Gebken, Bennet; Müller, Georg; Peitz, Sebastian; Volkwein, Stefan (arXiv:2402.06376)
The efficient optimization method for locally Lipschitz continuous multiobjective optimization problems from [1] is extended from finite-dimensional problems to general Hilbert spaces. The method iteratively computes Pareto critical points, where in each iteration, an approximation of the subdifferential is computed in an efficient manner and then used to compute a common descent direction for all objective functions. To prove convergence, we present some new optimality results for nonsmooth multiobjective optimization problems in Hilbert spaces. Using these, we can show that every accumulation point of the sequence generated by our algorithm is Pareto critical under common assumptions. Computational efficiency for finding Pareto critical points is numerically demonstrated for multiobjective optimal control of an obstacle problem.

Einfluss von Temperatur und Strömungsführung auf die NH3-SCO sowie die NH3-SCR mit Partikeln aus einer Sprayflammensynthese - Bablitzka, Nico Janosch; Beimdiek, Janis

Herstellung und Charakterisierung von Wood-Plastic-Composites (WPC) mit einer Matrix aus thermoplastischen Polyurethanen zur Erzeugung einer Holz-WPC-Verbundstruktur - Richters, Maximilian

An alternative and robust formulation of the fatigue crack growth rate curve for long cracks - Kullmer, Gunter; Weiß, Deborah; Schramm, Britta (Engineering Fracture Mechanics)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Zeit für das Leben - Notwendigkeit und Probleme einer zeitsensiblen Ethik - Meyer zu Hörste-Bührer, Raphaela (Ethik der Zeit - Zeiten der Ethik)

Ethik der Zeit - Zeiten der Ethik

Herausforderungen in der inklusiven Mädchenarbeit: Begleitforschung der „Inklusiven anonymen Zuflucht“ des Mädchenhaus Bielefeld e.V. - Richter, Susanne (Inklusiver Kinderschutz – Anforderungen, Herausforderungen, Perspektiven)

Distributed Control of Partial Differential Equations Using Convolutional Reinforcement Learning - Peitz, Sebastian; Stenner, Jan; Chidananda, Vikas; Wallscheid, Oliver; Brunton, Steven L.; Taira, Kunihiko (Physica D: Nonlinear Phenomena)
We present a convolutional framework which significantly reduces the complexity and thus, the computational effort for distributed reinforcement learning control of dynamical systems governed by partial differential equations (PDEs). Exploiting translational equivariances, the high-dimensional distributed control problem can be transformed into a multi-agent control problem with many identical, uncoupled agents. Furthermore, using the fact that information is transported with finite velocity in many cases, the dimension of the agents’ environment can be drastically reduced using a convolution operation over the state space of the PDE, by which we effectively tackle the curse of dimensionality otherwise present in deep reinforcement learning. In this setting, the complexity can be flexibly adjusted via the kernel width or by using a stride greater than one (meaning that we do not place an actuator at each sensor location). Moreover, scaling from smaller to larger domains – or the transfer between different domains – becomes a straightforward task requiring little effort. We demonstrate the performance of the proposed framework using several PDE examples with increasing complexity, where stabilization is achieved by training a low-dimensional deep deterministic policy gradient agent using minimal computing resources.

Kinderschutz im Wandel – methodologische Herausforderungen einer Ethnographie zur Institutionalisierung Früher Hilfen - Kelle, Helga; Edler, Amanda; Dahmen, Stephan (Zwischen Transformation und Tradierung – Qualitative Forschung zum Wandel pädagogischer Institutionen)

Der Imperativ der Biographisierung und die Ambivalenzen individueller Verantwortungszuschreibung - Dahmen, Stephan (Responsibilisierung)

Sinnvolle Ergänzung oder bewusster Bruch? - Tätigkeitsfelder im Berufsfeldpraktikum innerhalb des Lehramtsstudiums - Vogelsang, Christoph; Meier, Jana (Das Berufsfeldpraktikum als Professionalisierungselement - Grundlagen, Konzepte, Beispiele für das Lehramtsstudium)

Mediennutzung von Jugendlichen zu sozialen und politischen Fragen, schulische Aktivitäten und Lehrkräftefortbildungen - Welsandt, N.J.; Huschle, L.; Drossel, Kerstin; Deimel, D.; Abs, H.J. (ICCS 2022. Schulische Sozialisation und politische Bildung von 14-Jährigen im internationalen Vergleich)

A new mathematical formulation for the simultaneous optimization of charging infrastructure and vehicle schedules for electric bus systems - Stumpe, Miriam (Transportation Research Procedia)

Synergieeffekte zwischen Henze-Digital und der Carl Maria von Weber-Gesamtausgabe durch die bilaterale Weiterentwicklung der WeGA-WebApp - Ried, Dennis

Die Werkdatensätze von Henze-Digital als Ansätze für ein digitales Werkverzeichnis - Ried, Dennis (Die Tonkunst)